An evaluation of subsidized rural primary care programs: I. A typology of practice organizations. - Sheps, C G (1983)
The design of a comprehensive evaluation of subsidized rural primary care programs on a large national scale is described, Its major purpose is to derive data whose analysis will answer major policy questions about the factors influencing the outcome of the major types of such programs in different communities. This first paper also delineates a typology which was developed of five principal organizational forms of these programs. This classification appears to provide suitable operational definitions of forms of rural practice as a basis for evaluating the differential impact of alternative types of primary care programs.